Intra- and extra-uterine diagnosis and treatment of peripartum imperforate hymen: a case report - Bian, Wei; Gu, Jianmei; Yang, Juan; Wang, Yu (Frontiers in Pediatrics, 2025)
The article reports a case of fetal imperforate hymen diagnosed by prenatal MRI and confirmed by postnatal surgery. The pregnant woman underwent routine 37-week ultrasound examination, which revealed an enlarged fetal bladder and an abdominal cystic mass. Subsequent 37-week + 6 prenatal MRI showed fetal uterine and vaginal fluid accumulation, suggesting congenital vaginal atresia. At 39 weeks + 5, under ultrasound guidance, amniotic, fetal abdominal, and vaginal cyst fluid were aspirated through a maternal abdominal puncture, avoiding the bowel. The cysts were significantly reduced in size, and the patient delivered vaginally at 39 weeks + 6. On postpartum day 1, pelvic MRI of the neonate showed normal uterine and cervical anatomy, with a lengthened, thickened vaginal wall and no fluid collection. On postpartum day 2, the patient underwent surgical exploration, which confirmed the diagnosis of imperforate hymen. Partial hymenectomy was performed without complication.